Geschichtsschreibung in der Emigration - Meinschien, Birte (2020)
The work examines the lives, works, and impact of emigrated historians in Great Britain in the form of a collective biography. It investigates four major thematic areas: the historians' emigration and integration, their university careers, their research interests and methods, and their status among British and German historians.